FINANCIAL LITERACY OF FINANCIAL INSTITUTIONS IN BANGLADESH - Jakaria, Saleh Ahmed (Australian Finance & Banking Review, 2022)
This research delves into the financial literacy landscape of diverse financial institutions in Bangladesh. Using a mixed-methods approach, the study assesses financial literacy levels, identifies influencing factors, and explores collaborative efforts. Quantitative data gathered through surveys from 150 institutions reveal variations in financial literacy, with banks displaying higher scores (M = 75), followed by microfinance institutions (M = 62) and non-bank entities (M = 48). Qualitative interview insights highlight effective collaborative initiatives between institutions, regulators, and educational bodies. The study contributes novelty by presenting a holistic view of financial literacy, its associations, and implications within the sector. Findings resonate with previous research, linking financial literacy to risk management and ethical decision-making. The research underlines the need for tailored training programs and sustained collaborations. Future research could explore evolving regulatory dynamics and technological impacts. This research augments our understanding of financial literacy's importance and potential to enhance the resilience and inclusivity of Bangladesh's financial sector.JEL Classification Codes: O16 G21, G28, I22.